Diversity and ecology of bat flies (Diptera: Nycteribiidae, Streblidae) from Cat Ba National Park - Luong, Nguyen Thanh; Thinh, Ta Huy; Thong, Vu Dinh (Academia Journal of Biology, 2017)
Cat Ba National Park contains a high diversity fauna of bats including a species endemic to Vietnam. Since 1999, we conducted a series of bat surveys in the park with an investigation into bat files. All individuals of flies collected from each bat individual were preserved in a plastic tube filled with pure alcohol. They were analysed and identified at the Institute of Ecology and Biological Resources. Results from our research provide records of 8 bat fly species belonging to 4 genera, 2 families; of these, 3 species belong to the family Nycteribiidae (Basila roylii, B. burmensis, B. pundibunda) and 5 remaining ones belong the family Streblidae (Ascodipteron phyllorhinae, A. wenzeli, Brachytarsina amboiensis, B. cucullata, Maabella stomalata). These fly species parasitize 8 bat species belonging to 4 families: 5 species of Hipposideridae (Hipposideros alongensis, H. armiger, H. grandis, H. khoukhouayensis, H. pomona), 1 species of Miniopteridae (Miniopterus fuliginosus), 1 species of Rhinolophidae (Rhinolophus marshalli) and 1 species of Vespertilionidae (Hypsugo pulveratus). Basilia pundibunda was the most common bat fly species within the study area. The first data on ecological correlation between flies and bats from Vietnam were also recorded and given in this paper. Citation: Nguyen Thanh Luong, Ta Huy Thinh, Vu Dinh Thong, 2018. Diversity and ecology of bat flies (Diptera: Nycteribiidae, Streblidae) from Cat Ba National Park. Tap chi Sinh hoc, 40(1): x-xx. DOI: 10.15625/0866-7160/v40n1.10746. *Corresponding author: vudinhthong@hotmail.com Received 22 September 2017, accepted 2 December 2017